Parallelized Reaction Pathway and Stronger Internal Band Bending by Partial Oxidation of Metal Sulfide-Graphene Composites: Important Factors of Synergistic Oxygen Evolution Reaction Enhancement - Han, HyukSu; Kim, Kang Min; Choi, Heechae; Ali, Ghulam; Chung, Kyung Yoon; Hong, Yu-Rim; Choi, Junghyun; Kwon, Jiseok; Lee, Seung Woo; Lee, Jae Woong; Ryu, Jeong Ho; Song, Taeseup; et al. (AMER CHEMICAL SOC, 2018)
The electrocatalytic performance of transition metal sulfide (TMS) graphene composites has been simply regarded as the results of high conductivity and the large surface/volume ratio. However, unavoidable factors such as degree of oxidation of TMSs have been hardly considered for the origin of this catalytic activity of TMS-graphene composites. To accomplish the reliable application of TMS-based electrocatalytic materials, a clear understanding of the thermodynamic stability of TMS and effects of oxidation on catalytic activity is necessary. In addition, the mechanism of charge transfer at the TMS-graphene interface must be studied in depth to properly design composite materials. Herein, we report a comprehensive study of the physical chemistry at the junction of a Co1-xNixS2-graphene composite, which is a prototype designed to unravel the mechanisms of charge transfer between TMS and graphene. Specifically, the thermodynamic stability and the effects of oxidation of TMSs during the oxygen evolution reaction (OER) on the reaction mechanism are systematically investigated using density functional theory (DFT) calculations and experimental observations. Cobalt atoms anchored on pyridinic N sites in the graphene support form metal semiconductor (SC) junctions, and the internal band bending at these junctions facilitates electron transfer from TMSs to graphene. The junction enables fast sinking of the excess electron from OH- adsorbate. Partially oxidized amorphous TMS layers formed during the OER can facilitate adsorption and desorption of OH and H atoms, boosting the OER performance of TMS graphene nanocomposites. From the DFT calculations, the enhanced electrocatalytic activity of TMS graphene nanocomposites originates from two important factors: (i) increased internal band bending and (ii) parallelized OER pathways at the interface of pristine and oxidized TMSs.
Keywords: LITHIUM-ION BATTERIES; HYDROGEN EVOLUTION; IN-SITU; WATER OXIDATION; DOPED GRAPHENE; BIFUNCTIONAL ELECTROCATALYST; REDUCTION REACTION; REDUCED GRAPHENE; EFFICIENT ELECTROCATALYST; HIGHLY EFFICIENT